Tool Wear Analysis of Coated Carbide Tools on Cutting Force in Machining Process of AISI 4140 Steel. Issue 1 (July 2020) - Lubis, Sobron; Rosehan,; Darmawan, Steven; Indra, Benny
Abstract: In manufacturing industries specifically in metal machining, the use of the cutting tool is important to consider. The use of the cutting tool has not been used optimally, as well as cutting parameters. In the cutting process, the wear of the cutting tool and cutting force has a very close relationship. This research was carried out to analyze the wear of coated carbide cutting tool and cutting forces produced in turning AISI 4140 steel workpieces. This study was conducted with a variation of five cutting speed levels consisting of 180 m/min, 220 m/min, 260 m/min, 300 m/min, 340 m/min and depth of cut 0.7 mm. To observe the tool wear, every 5 minutes with a maximum limit value of VB of 0.3 mm and for the cutting force values taken every 1 minute. From the results of the study obtained: The increase in the value of the cutting force is affected by the increase in wear that occurs in the cutting tool due to a change in tool geometry due to wear on the cutting tool. The highest feeding force value is at the cutting speed (Vc) 340 m / min at 368 N and the greatest cutting force value is at the cutting speed (Vc) 340 m / min at 371 N.